Exploring Immersion Coating as a Cost-Effective Method for Small-Scale Production of Enteric-Coated Gelatin Capsules - Beatrice Sabbatini; Diego Romano Perinelli; Giovanni Filippo Palmieri; Marco Cespi; Giulia Bonacucina (MDPI AG, 2024)
The coating process for solid dosage forms is widely used in the pharmaceutical industry but presents challenges for small-scale production, needed in personalized medicine and clinical or galenic settings. This study aimed to evaluate immersion coating, a cost-effective small-scale method, for enteric-coated gelatin capsules using standard equipment. Two enteric coating polymers and different polymer concentrations were tested, along with API solubility. Results were compared with commercially available enteric capsule shells. Successful preparation of enteric coating capsules via immersion necessitates a comprehensive grasp of API and enteric polymer behavior. However, utilizing commercially available enteric capsule shells does not guarantee ease or robustness, as their efficacy hinges on the attributes of the active ingredient and excipients. Notably, coating with Eudragit S100 stands out for its superior process robustness, requiring minimal or no development time, thus representing the best option for small-scale enteric capsule production.